2020
DOI: 10.3390/biomedicines8070183
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Metabolism is Associated with DNA Repair Genes in Breast and Colorectal Cancer. Screening of Potential Progression Markers Using qPCR

Abstract: In this work, we compared mRNA levels of Hyaluronan (HA) metabolism members and BRCA genes, known to be involved in the tumoral process, between tumor and non-tumor adjacent tissue and its correlation with previously proposed biomarkers (ER, PR, HER2 and KI67) in order to assess their value as a progression biomarkers. We show alteration in HA metabolism in colorectal but not breast cancer. However, we found a decrease in Hyaluronidase 1 HYAL1 levels in the breast but not colorectal cancer. We also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In agreement with previous findings in MDA-MB-231 cells with the reduced expression of the PG/GAG linker region biosynthetic enzyme ß4GALT7 [25], a reduced expression of Sdc-1 was associated with an upregulation of HAS2 in MCF-7 cells, while the expression of HA receptor, RHAMM, was downregulated. Notably, previous reports have shown that HA secretion is higher in MDA-MD-231 than MCF-7 and is in correlation with ER-negative status [37], but both cell lines express a similar level of mRNA HAS-2 and its gene expression is not associated with hormonal receptors' ER/PR status [38,39]. Therefore, our results acquire significant weight to demonstrate that Sdc-1 and HA metabolism are functionally related, whereas Sdc-1 depletion also affected the HA signaling pathway in MDA-MB-231 cells, however, in a differential manner.…”
Section: Discussionmentioning
confidence: 90%
“…In agreement with previous findings in MDA-MB-231 cells with the reduced expression of the PG/GAG linker region biosynthetic enzyme ß4GALT7 [25], a reduced expression of Sdc-1 was associated with an upregulation of HAS2 in MCF-7 cells, while the expression of HA receptor, RHAMM, was downregulated. Notably, previous reports have shown that HA secretion is higher in MDA-MD-231 than MCF-7 and is in correlation with ER-negative status [37], but both cell lines express a similar level of mRNA HAS-2 and its gene expression is not associated with hormonal receptors' ER/PR status [38,39]. Therefore, our results acquire significant weight to demonstrate that Sdc-1 and HA metabolism are functionally related, whereas Sdc-1 depletion also affected the HA signaling pathway in MDA-MB-231 cells, however, in a differential manner.…”
Section: Discussionmentioning
confidence: 90%
“…We extended the study by evaluating patients with breast cancer, using samples obtained from patients in the Hospital of our region. In the present study, we analyzed the expression of UGDH mRNA in tumoral (TT) and normal adjacent tissue (NAT) samples obtained from four breast cancer patients previously characterized according to ER, PR, HER2 and Ki67 status in our laboratory [ 34 ]. In three patients who were defined as HER2−, we observed an increase in UGDH expression in TT compared to NAT.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found when evaluating the expression of UGDH in breast cancer cell lines with different aggressive phenotypes and ER, PR and HER2 status. On the other hand, the patient that showed a decrease in UGDH levels showed also a decrease in HA expression and HAS2 levels [ 34 ]. Although further studies are required to understand the function of this enzyme in breast cancer patients and its relation with HA metabolism, these results confirm the data observed in vitro and in silico, and indicate that the mechanisms in which UGDH is involved could be altered during breast cancer progression and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation